Somewhat Opinionated A New York dance journal - Barnes, Clive 1927-2008 (Dance Books Ltd., Alton,Hampshire (UK), 2008)
New York City Center 7-21 October New York City Center 23 October-4 November New York City Center 14-18 November New York State Theater 20 November-7 February New York City Center 28 November-30 December PALABRAS CLAVE: The Wheeldon Company, American Ballet Theatre, Pennsylvania Ballet, Lincoln Kirstein, New York City Ballet, Alvin Ailey American Dance Theater